Efektivitas Pemenuhan Nafkah Anak Pasca perceraian Di Pengadilan Agama Palu Kelas Ia - Fatimawali (Amorti: Jurnal Studi Islam Interdisipliner, 2025)
Divorce terminates the marital relationship but does not end parental responsibility for children. This study examines the effectiveness of post divorce child maintenance at the Palu Religious Court Class IA, identifies the factors that obstruct its implementation, and formulates a strengthening model oriented toward children’s best interests. The study employed a descriptive qualitative design. Data were obtained through semi-structured interviews with six purposively selected informants one judge, one court registrar, two heads of Religious Affairs Offices, and two parents affected by divorce supported by document review and observation. Data were analysed through reduction, categorisation, interpretation, and source triangulation. The findings reveal three implementation patterns: regular payment, irregular payment, and complete non-payment. Court judgments have provided a formal legal basis, yet substantive effectiveness remains weak because payment still depends largely on fathers’ voluntary compliance. The principal barriers are weak parental responsibility, unstable income, post-divorce communication conflict, passive post-judgment supervision, and limited access to enforcement. The study also identifies a kinship-buffer paradox: extended families protect children when fathers fail to pay, but their assistance can unintentionally normalise paternal non-compliance and shift the economic burden to the maternal family. Strengthening implementation therefore requires operational court orders, child-focused co-parenting communication, extended-family mediation that does not replace paternal responsibility, and accessible enforcement procedures. These measures accord with maqāṣid al-syarī‘ah by protecting children’s life, intellect, lineage, property, and dignity This is an open-access article under the CC–BY-SA license.